Sry‐like high‐mobility group box antibody‐related paraneoplastic cerebellar degeneration in the background of underlying non‐small cell lung cancer. Issue 3 (31st May 2016) - Onder, Halil; Kurtulan, Olcay
Abstract: Paraneoplastic neurological syndromes (PNS) are defined as all non‐metastatic neurological complications of cancer in which no other etiologies, such as vascular, infectious or metabolic, were determined. Recently, Sry‐like high‐mobility group box (SOX1) antibody associated with PNS has been described, and is associated with Lambert–Eaton myasthenic syndrome, paraneoplastic cerebellar degeneration and paraneoplastic peripheral neuropathy invariably in the background of underlying small‐cell lung cancer. A 75‐year‐old man was admitted to our neurology clinic at Hacettepe University Hospital, Sihhiye, Ankara, Turkey with complaints of imbalance and memory impairment that had started 2 months earlier and progressively increased. Neurological examination showed a state of delirium in the background of rapid progressive dementia and severely truncal ataxia. Cranial magnetic resonance imaging was unremarkable; however, in further investigations, thoracic tomography yielded bilateral hilar lymphadenopathy, and paraneoplastic antibody investigations resulted in positive SOX1 antibody. The following thoracic excisional lymph node biopsy investigations supported the diagnosis of non‐small‐cell lung cancer and paraneoplastic cerebellar degeneration associated with SOX1 antibody in the background of non‐small‐cell lung cancer. Adjuvant chemotherapy was started, but the patient deteriorated, which prevented proper plasmapheresis therapy. He died in the second month of admission as a result of severe sepsis leading to septic shock. Here, we show the second case diagnosed with PNS in association with non‐small‐cell lung cancer. We note the importance of SOX1 antibody as a marker for PNS, and suggest that investigations of this antibody be carried out in larger case studies. Abstract : Herein, we present a patient SOX1 antibody associated paraneoplastic cerebellar degeneration (PCD) who was diagnosed with non‐SCLC lung cancer. Via this report we suggest SOX1 antibody as a possible screening target for PCD in patients with non‐SCLC other than SCLC and remark the neccesity of related future studies of larger case series